A Sequential Implementation Model for Workforce Development: A Case Study of Medical Residency Training for Substance Use Concerns. Issue 1 (2nd January 2018) - O'Sullivan, Patricia S.; Yuan, Patrick; Satre, Derek D.; Wamsley, Maria; Satterfield, Jason
ABSTRACT: Problem: In graduate medical education, residency programs are often educationally isolated from each other, with varying needs and patient populations, so strategies are needed when attempting to implement training in evidence-based practices across multiple residencies. Intervention: Using implementation science as a guide, we adapted a community development model to sequentially implement an evidence-based intervention, Screening, Brief Intervention, and Referral to Treatment (SBIRT) for alcohol and drug use problems, across internal medicine, pediatrics, emergency medicine, psychiatry, and obstetrics and gynecology residency programs. Context: A grant-funded "executive" team coordinated the implementation, enrolled a new residency program annually, and served as the consultative team to span the programs. The team was attentive to aligning implementation with the needs of each program. To assist in planning, the team included a program champion 1 year prior to SBIRT implementation to provide the opportunity to develop resources and work with peers. We evaluated this model through an implementation science lens using a case study approach that included interviews and quantitative tabulation of products and resident perceptions. Outcome: We successfully instituted SBIRT training in all 5 residency programs through the use of a supported local champion model. Teams developed 90 curricular products and had 57 presentations and publications. Residents reported satisfaction with the SBIRT activities. Champions reported that SBIRT was a useful approach and that they gained valuable knowledge and relationships from working with the executive team when designing learning materials appropriate for their residency. Champions successfully incorporated SBIRT into routine clinical practice. Lessons Learned: Having a strong team to support subsequent SBIRT champions was essential for implementation. The champions needed financial support to have the necessary time to implement training. The strategy of building a peer network across programs was critical for sustaining the implementation. Collecting and sharing resources aided the champions in developing their materials.